THE GLOBAL SIGNIFICANCE OF THE SCIENCE OF HADITH SULTAN IMAM BUKHORI'S WORKS - Matluba Tokhtaeva (Journals Park Publishing, 2022)
In the article, preserving the purity of Islam, revealing its true essence, promoting pure faith is related to the life and spiritual heritage of the great scholar Imam Bukhari, Imam Bukhari's attitude to the science of hadith, dividing them into sahih (true, reliable) and non-authentic, and their evil, identification, study and research of hadith narrators, the fairness of their narrations, researching various issues of the science of hadith, their interest in issues such as summarizing and studying them in connection with the verses of the Quran, and during the analysis of the works, the great educational value of the spiritual heritage of scholars was studied.
Keywords: authentic hadiths, hadith studies, Islamic culture, hadiths about manners, starting good with relatives, educating in the spirit of manners.